1996
DOI: 10.1107/s0907444995014119
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Human Salivary α-Amylase at 1.6 Å Resolution: Implications for its Role in the Oral Cavity

Abstract: Salivary a-amylase, a major component of human saliva, plays a role in the initial digestion of starch and may be involved in the colonization of bacteria involved in early dental plaque formation. The three-dimensional atomic structure of salivary amylase has been determined to understand the structure-function relationships of this enzyme. This structure was refined to an R value of 18.4% with 496 amino-acid residues, one calcium ion, one chloride ion and 170 water molecules. Salivary amylase folds into a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
205
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(214 citation statements)
references
References 42 publications
6
205
0
3
Order By: Relevance
“…The wide range of known three-dimensional structures of a-amylases from Aspergillus oryzae (Matsuura et al, 1984;Swift et al, 1991), Aspergillus niger (Boel et al, 1990;Brady et al, 1991), porcine pancreas (Buisson et al, 1987;Qian et al, 1993;Larson et al. 1994), barley seeds (Kadziola et al, 1994), Bacillus lichenifomis (Machius et al, 1995), human pancreas (Brayer et al, 1995), and human salivary (Ramasubbu et al, 1996) constitute an ideal system for studies of adaptation of enzymes to extreme conditions on a molecular level. The three-dimensional structures obtained and described in this paper provide new insights into the mechanism of cold adaptation.…”
Section: Activity At Low Temperaturementioning
confidence: 99%
“…The wide range of known three-dimensional structures of a-amylases from Aspergillus oryzae (Matsuura et al, 1984;Swift et al, 1991), Aspergillus niger (Boel et al, 1990;Brady et al, 1991), porcine pancreas (Buisson et al, 1987;Qian et al, 1993;Larson et al. 1994), barley seeds (Kadziola et al, 1994), Bacillus lichenifomis (Machius et al, 1995), human pancreas (Brayer et al, 1995), and human salivary (Ramasubbu et al, 1996) constitute an ideal system for studies of adaptation of enzymes to extreme conditions on a molecular level. The three-dimensional structures obtained and described in this paper provide new insights into the mechanism of cold adaptation.…”
Section: Activity At Low Temperaturementioning
confidence: 99%
“…These Cl − -dependent α-amylases are usually specific to all mammalian species, but are also found in a few types of bacteria, such as Pseudoalteromonas haloplanktis (D' Amico et al 2000). The solved structures of chloride-dependent α-amylases from human salivary (Ramasubbu et al 1996) and pancreatic (Brayer et al 1995) glands, porcine pancreas (Qian et al 1993;Larson et al 1994), Tenebrio molitor (Strobl et al 1998), and P. haloplanktis (Aghajari et al 2002) contain the ion at a common site, which is located close to the center of the (β/α) 8 -barrel and in the near vicinity of the catalytic site. The protein ligands for the chloride ion and the interaction network within the active site have been elucidated (Aghajari et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…A study of P. haloplanctis α-amylase has revealed that Cl − can interact with active site carboxylates and the protective effect against Ca 2+ inhibition is consistent with the appearance of a protonated carboxyl group upon Cl − binding (Feller et al 1996). The chloride-binding site of mammalian pancreatic and salivary α-amylases consists of Arg195, Asn298, the side-chain amines of Arg337, and a water molecule (Brady et al 1991;Qian et al 1993;Lawson et al 1994;Ramasubbu et al 1996). This binding site of Bl TreA differs from them by a tyrosine residue instead of Arg337 (Fig.…”
Section: Binding Of Monovalent Ionsmentioning
confidence: 99%
See 2 more Smart Citations